MANAGERIAL DECISION MAKING AUGMENTATION THROUGHOUT INFORMATION SOLUTIONS: THE CONCEPTUAL SYSTEM - Solczak, Robert (My University, 2015)
The dynamism of the environment where decisions are being performed becomes ever more turbulent. Strategic thinker in order to drive his organization towards success and sustain it on a competitive level must take fast actions and consider vast number of complex factors. This requires deep insight into the organization and fast way of processing data in order to develop possibly unambiguous judgments. Human mind, without any support, would not cope with processing such amount of information what would lead to poor managerial decision. It is known that human requires support of his cognitive thinking processes and current technology harnessed in appropriate way would enable decision maker to perform fast, yet precise decisions that are crucial for enterprise to successfully compete on the turbulent market. This thesis introduces a conceptual system of decision making augmentation. Such system would harness the modern processing power of computers within an ERP based infrastructure to collect data from across the organization and process it accordingly. Processed, grouped, and filtered data would be presented via graphical, interactive, and highly adaptive interface allowing decision maker to quickly analyze data and simulate possible opportunities in order to perform high quality decision making. This concept is built on theory review synthetized in context of the idea; three propositions build a core of the further analysis which at last creates a foundation for the system development. This thesis does not introduce to technical aspects of the system but to an idea of how decision maker and organization could potentially benefit from it.
Keywords: ERP; Augmentation; Decision Making; Organizational Performance Optimization; Dynamic Strategy; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|